DIGESTIBILITY ON LOCAL FEMALE RABBIT FED DIETS CONTAINING DIFFERENT LEVELS OF FERMENTED TOFU WASTE - I M., Nuriyasa; Puger, A. W. (Majalah Ilmiah Peternakan; Vol 22 No 2 (2019): Vol. 22 No.2 (2019), 2019)
This study aims to determine the digestibility of local female rabbit fed diet containing different levels of fermented tofu waste. The study used a randomized block design (RBD), with five treatments and five blocks. The treatment was rabbits fed rations without using tofu waste or control fed (R0), rabbit fed rations containing 10% tofu waste (R1), rabbit fed containing 15% tofu waste (R2), rabbit fed rations containing 10% fermented tofu waste (R3) and rabbit fed rations containing 15% fermented tofu waste (R4). Variables observed were dry matter digestibility, protein digestibility and efficiency of changes GE to DE. The results showed that rabbits fed ration R3 and R4 caused dry matter digestibility, protein digestibility and efficiency of changes GE to DE were higher than treatments R2, R1 and R0. It can be concluded that diets containing 10% up to 15% fermented tofu waste in rabbit rations can increase the digestibility of rations for local female rabbits.